2011
DOI: 10.1016/j.jconrel.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated tumor imaging and nanotherapy using drug loaded, block copolymer stabilized perfluorocarbon nanoemulsions

Abstract: Perfluorocarbon nanoemulsions can deliver lipophilic therapeutic agents to solid tumors and simultaneously provide for monitoring nanocarrier biodistribution via ultrasonography and/or 19F MRI. In the first generation of block copolymer stabilized perfluorocarbon nanoemulsions, perfluoropentane (PFP) was used as the droplet forming compound. Although manifesting excellent therapeutic and ultrasound imaging properties, PFP nanoemulsions were unstable at storage, difficult to handle, and underwent hard to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
399
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(421 citation statements)
references
References 99 publications
8
399
0
3
Order By: Relevance
“…17,18 Ultrasound waves can induce thermal and/or mechanical effects that could trigger the release of the drug from a collection of nanocarriers, such as liposomes, micelles, microbubbles, etc. 16 Moreover, advances in sonochemistry have shown that ultrasound-induced chemical reactions can differ from those carried out by bulk heating, implying mechanical or thermal effects at the nanoscale.…”
mentioning
confidence: 99%
“…17,18 Ultrasound waves can induce thermal and/or mechanical effects that could trigger the release of the drug from a collection of nanocarriers, such as liposomes, micelles, microbubbles, etc. 16 Moreover, advances in sonochemistry have shown that ultrasound-induced chemical reactions can differ from those carried out by bulk heating, implying mechanical or thermal effects at the nanoscale.…”
mentioning
confidence: 99%
“…Thereby, the traditional therapeutic efficacy are dramatically increased as a result of the enhancement of intracellular uptake on nanoparticles, genes, and drugs [19,29,[102][103][104][105]. …”
Section: Mechanical Action Of Non-cavitationmentioning
confidence: 99%
“…The phase-transition PFC nanoparticles as effective drug carriers were first reported in this study on account of the regression of tumor growth using PFP droplets to successfully deliver doxorubicin (DOX) into tumor tissues. And then, more valuable work has been explored by Rapoport [12,19,29,103] et al For instance, the PFC nanoemulsions encapsulated paclitaxel (PTX) can enhance the ultrasoundmediated tumor imaging on the ultrasonic therapy of pancreatic cancer and breast cancer in animal models due to the significant therapeutic characterizations based on tumor regression and suppression of metastasis [29].…”
Section: Cancer Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the use of liquid perfluorocarbons is that they can be emulsified in water when stabilized by an appropriate surfactant (e.g. pluronic, lipids) [34][35][36]. Such nanodroplets are typically smaller than 200 nm, which allows them to extravasate from the leaky tumor vasculature [37].…”
Section: In Situ Generation Of Microbubbles From Nanodropletsmentioning
confidence: 99%